EFIKASI DIRI IBU TERHADAP EFEKTIFITAS MENYUSUI IBU POST PARTUM - Asrianti Safitri Muchtar; A Ulfa Fatmasanti; Musni Musni; Ita Novianti (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
ABSTRACT MOM'S SELF EFFICIENCY TOWARDS THE EFFECTIVENESS OF POST PARTUM BREASTFEEDING Background: Breastfeeding self-efficacy is the mother's confidence in perceiving breastfeeding ability. Breastfeeding self-efficacy will determine individual responses in the form of choices for breastfeeding behavior, efforts and abilities to face breastfeeding challenges, patterns of thought and actions, mother's emotional reactions. These consequences determine the performance of breastfeeding initiation, and the duration of breastfeeding.Purpose: to determine the effect of mother's self-efficacy on the effectiveness of breastfeeding in the Bajoe Community Health Center, Bone Regency in 2020.Method: This study used a cross sectional study approach. The data obtained from the results of this study are quantitative data. The sample in this study were all postpartum mothers from June to September in the Bajoe Community Health Center with a total sample size of 46 people. The sampling technique used total sampling. The data analysis used was univariate and bivariate analysis presented in the frequency distribution table. For statistical tests, the level of significance used was p <0.05. The analysis used to determine the effect of self-efficacy of breastfeeding mothers on the effectiveness of breastfeeding was by using the chi square test and presented in the form of a frequency distribution table.Results: Based on the results of statistical tests using chi square, it was found that there was an effect of mother's self-efficacy on the effectiveness of breastfeeding with a value of p = 0.000, namely p value <0.005 so that there was an effect of mother's self-efficacy on the effectiveness of breastfeeding in the Bajoe Community Health Center, Bone Regency.Conclusion: There is a significant influence between mother's self-efficacy on breastfeeding effectiveness in the Bajoe Community Health Center, Bone Regency.Suggestion: It is hoped that mothers will increasa their breastfeeding self-efficacy by always increasing their knowledge about breast milk and breastfeeding so that they are able to breastfeed their babies effectively. For research sites, it is hoped that health education about breast milk and breastfeeding since the prenatal period can be routinely increased so as to increase the self-efficacy of mothers in the process of breastfeeding their babies. Keywords: Breastfeeding, Efficacy, Effective ABSTRAK Latar Belakang: Breastfeeding self-eficacy adalah kepercayaan diri ibu dalam mempersepsikan kemampuan menyusui. Breastfeeding self efficacy akan menentukan respon individu berupa pilihan atas perilaku menyusui, upaya dan kesanggupan menghadapi tantangan menyusui, pola pemikiran dan tindakan, reaksi emosional ibu. Konsekuensi ini menentukan performa inisiasi menyusui, dan durasi menyusui.Tujuan: untuk mengetahui pengaruh efikasi diri ibu terhadap efektifitas menyusui di wilayah kerja Puskesmas Bajoe Kabupaten Bone tahun 2020.Metode penelitian: Penelitian ini menggunakan pendekatan cross sectional study. Data yang diperoleh dari hasil penelitian ini berupa data kuantitatif. Sampel dalam penelitian ini adalah semua ibu postpartum pada bulan Juni – September di wilayah kerja puskesmas Bajoe dengan jumlah sampel sebesar 46 orang. Teknik pengambilan sampel menggunakan total sampling.Analisis data yang digunakan adalah analisis univariat dan bivariat disajikan dalam tabel distribusi frekuensi. Untuk uji statistik, tingkat kemaknaan yang digunakan p < 0,05. Analisis yang digunakan untuk mengetahui pengaruh efikasi diri ibu menyusui terhadap efektifitas menyusui adalahdengan uji chi squareserta disajikan dalam bentuk tabel distribusi frekuensi.Hasil: Berdasarkan hasil uji statistic menggunakan chi square didapatkan ada pengaruh efikasi diri ibu terhadapa efektifitas menyususi dengan nilai p= 0,000 yaitu p value < 0,005 sehingga ada pengaruh efikasi diri ibu terhadap efektifitas menyusui di wilayah kerja Puskesmas Bajoe Kabupaten Bone.Kesimpulan: Terdapat pengaruh yang signifikan antara efikasi diri ibu terhadap efektifitas menyusui di wilayah kerja Puskesmas Bajoe Kabupaten Bone.Saran: Diharapkan ibu lebih meningkatkan kepercayaan diri dalam proses pemberian ASI dengan selalu meningkatkan pengetahuan tentang ASI dan menyusui sehingga ibu mampu menyusui bayinya secara efektif. Bagi tempat penelitian diharapkan memberikan pendidikan kesehatan tentang ASI dan menyusui sejak masa prenatal secara rutin sehingga mampu meningkatkan kepercayaan diri ibu dalam proses menyusui bayinya. Kata Kunci: Menyusui, Efikasi, Efektifitas